SYSTEMATIC LITERATURE REVIEW: THE DYNAMIC IMPACTS OF CARBON EMISSIONS AND INVESTMENT IN THE G20 FORUM: TINJAUAN PUSTAKA SISTEMATIS: DAMPAK DINAMIS EMISI KARBON DAN INVESTASI DI FORUM G20 - Pancasari, Devi (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
This study aims to determine the relationship between renewable energy and investment in the G20 forum. The Kitchenham Systematic Literature Review (SLR) approach uses three main databases, namely Scopus, Springer, and Google Scholar. The final results obtained 11 articles published between 2019 and 2022. Thus this research provides knowledge about the importance of renewable energy and investment that can be used further and its relation to sustainable economic development